DEVELOPING TEACHING MATERIALS BASED ON DIGITAL VISUAL LITERACY - Noor Faridha; Alissa Ernawati Adisiswanto; Vina Rahma (UIBU, 2023)
The aims of this study were to: (1) provide teaching materials for students of State Administration, FISIP, and UMSJ in the form of English language modules; and (2) determine the feasibility of teaching materials in the form of English language modules. Research and Development (R&D) research designs, or research that is utilized to create specific goods and evaluate their viability. This research is a research development project (Research and Development). The four-D (4D) development model is the basis for the research design, which has four key stages: (1) define; (2) design; (3) develop, and (4) deploy. In this study, questionnaires and focus group discussions (FGD) were used to collect data. In learning, having access to educational resources is very important. This is because this teaching material contains information about English for Special Purposes courses offered by the State Administration Study Program, FISIP, and UMSJ. Based on preliminary observations made in the speaking class of semester 1 students of the State Administration Study Program at Moch Sroedji University, several deficiencies were found in terms of teaching English speaking: (1) the lecturer's speaking teaching method was less varied (2) the lecturer did not use appropriate media/techniques the theme to be discussed in the speaking course; and (3) learning to speak seems monotonous and boring. Increasing literacy through digital visual literacy is one way to work around this. This ability can be developed with the help of visual media literacy. Researchers adapted the model (Gall, 2003) in this study, which includes needs analysis, product development, expert validation, revision, and testing and modification. At the needs analysis stage, researchers conducted interviews with lecturers and students. Based on the results of the needs analysis, they need literacy and strategies to help them improve their speaking skills.